Laser Assisted Growth Of ZnO Structures In Selected Locations For Photodetectors - Lahewil, Abdulwahab Salem Zaroug (2023)
The exceptional characteristics of one-dimensional zinc oxide (ZnO), which has applications in electrical, electrochemical, electromechanical, and sensing devices, make it one of the most promising nanostructures. At various continuous laser irradiation times of 20, 25, and 30 minutes, respectively, utilizing a simple and quick laser-assisted chemical bath deposition (LACBD) method on glass substrates with a three-hours post-annealing at 400 oC. Functional ZnO nanostructures known as micronanorods with satisfactory structural, morphological, and optical properties were grown on a glass substrate coated with various metal buffer layers of nickel (Ni), titanium (Ti), using RF sputtering, and iron (Fe), using thermal evaporation. Variation in morphology analysis, crystallinity, and the optical spectra of reflectance, absorption, and transmission have been investigated, discussed, and connected with changes in laser irradiation periods, respectively. The XRD patterns showed that the synthesized material had a strong ZnO MRs (002) peak, a hexagonal wurtzite structure, and exhibited a preferred orientation along with the c-axis orientation for all the samples. The crystallite grain size increased and was found to be in the range of 8.88 nm to 12.16 nm for the samples using Ni, 4.772 nm to 11.955 nm for the samples using Ti, and 11.699 nm for the samples using Fe buffer layers, respectively. The energydispersive X-ray (EDX) analysis was used to identify the components and confirm that the required composition was present.